Theranostic applications of peptide-based nanoformulations for growth factor defective cancers - Ghosh, Arnab; Maske, Priyanka; Patel, Vinay; Dubey, Jyoti; Aniket, Kundu; Srivastava, Rohit (International journal of biological macromolecules, 2024)
Growth factors play a pivotal role in orchestrating cellular growth and division by binding to specific cell surface receptors. Dysregulation of growth factor production or activity can contribute to the uncontrolled cell proliferation observed in cancer. Peptide-based nanoformulations (PNFs) have emerged as promising therapeutic strategies for growth factor-deficient cancers. PNFs offer multifaceted capabilities including targeted delivery, imaging modalities, combination therapies, resistance modulation, and personalized medicine approaches. Nevertheless, several challenges remain, including limited specificity, stability, pharmacokinetics, tissue penetration, toxicity, and immunogenicity. To address these challenges and optimize PNFs for clinical translation, in-depth investigations are warranted. Future research should focus on elucidating the intricate interplay between peptides and nanoparticles, developing robust spectroscopic and computational methodologies, and establishing a comprehensive understanding of the structure-activity relationship governing peptide-nanoparticle interactions. Bridging these knowledge gaps will propel the translation of peptide-nanoparticle therapies from bench to bedside. While a few peptide-nanoparticle drugs have obtained FDA approval for cancer treatment, the integration of nanostructured platforms with peptide-based medications holds tremendous potential to expedite the implementation of innovative anticancer interventions. Therefore, growth factor-deficient cancers present both challenges and opportunities for targeted therapeutic interventions, with peptide-based nanoformulations positioned as a promising avenue. Nonetheless, concerted research and development endeavors are essential to optimize the specificity, stability, and safety profiles of PNFs, thereby advancing the field of peptide-based nanotherapeutics in the realm of oncology research. The graphical abstract concerns theranostic applications of peptide-based nanoparticles in growth factor defective cancers. They can carry drugs or gene-silencing molecules to the cancer cells as cargo, bind to specific receptors on the cancer cells and enter them. The particles then release their cargo inside the cells and kill them. This approach is claimed to be more selective, flexible, and effective than traditional therapies, subject to more clinical data from large-scale human trials. Efforts are more towards increasing the scalability of this technology. [Display omitted]